ASSESSMENT OF THE MATERNAL VENOUS CIRCULATION: WHY IS IT RELEVANT?. (6th December 2013) - TOMSIN, KATHLEEN; GYSELAERS, WILFRIED
Abstract : The venous system is considered the main capacitor of the human body. Approximately 70% of the total blood volume resides in the venous bed, half of which circulates as venous return whereas the other half functions as reserve volume in the splanchnic veins. These veins are richly innervated and highly compliant, and communicate with the systemic circulation via capillaries (entrance) and portal vein and liver (exit). This constitution allows the venous compartment to balance circulating and stored blood volumes, and thus control cardiac output. Clinical conditions with reduced cardiac output are often associated with hampered venous return, resulting in visceral oedema, ascites or organ dysfunction. Organ dysfunction or failure may also result from (sub)obstructed venous outflow, as is illustrated in renal vein thrombosis or in the Nutcracker syndrome. Recently, the application of Doppler ultrasonography in the study of the maternal venous system illustrated that preeclampsia is another cardiovascular disorder with dysfunctional venous haemodynamics. In this opinion paper, we summarise results from Doppler studies of the maternal venous compartment, illustrating that performing venous haemodynamics function tests is to become a fundamental part of an integrated cardiovascular assessment of women with hypertension in pregnancy, facilitating an individualised diagnostic and therapeutic approach for every woman at risk for gestational hypertensive disease.